Soil respiration in Patagonian semiarid grasslands under contrasting environmental and use conditions - Peri, Pablo Luis (2015)
Grasslands comprise 85% of Southern Patagonia land area and play a critical role in the global carbon cycle. We evaluated seasonal dynamics to identify differences in soil respiration rates between contrasting grasslands across a climate gradient (rainfall), long term grazing intensity (moderate and high stocking rates) and land uses (silvopastoral system, primary forest and grassland). Soil respiration varied from 0.09 g CO2 h-1 m-2 in winter to a maximum of 1.43 g CO2 h-1 m-2 in spring. We found that the soil respiration rate was 30% higher in moderately grazed grasslands than in heavily grazed grasslands. Land-use changes showed that soil respiration followed the order silvopastoral system > native forest > grassland. While almost all plant and soil variables had a significant effect on soil respiration, soil carbon concentration, litter cover and depth and bare soil cover were the main factors explaining 78-83% of the variance in soil respiration. Soil respiration rates were correlated strongly to air and soil temperatures and to a lesser extent with mean monthly rainfall and soil volumetric water content. The information provided in the present work about soil respiration is essential to estimate carbon balance for a range of important and widespread ecosystems in Patagonia.